College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 8, Sequences and Series - Section 8.6 - The Binomial Theorem - 8.6 Exercises: 51

Answer

Yes, the statement is true.

Work Step by Step

$\displaystyle \left(\begin{array}{l}n\\1\end{array}\right)=\frac{n!}{1!(n-1)!}=\frac{n(n-1)!}{1*(n-1)!}=\frac{n}{1}=n$ $\displaystyle \left(\begin{array}{l} n\\n-1\end{array}\right)=\frac{n!}{(n-1)!1!}=\frac{n(n-1)!}{(n-1)!*1}=\frac{n}{1}=n$ Thus we have shown that: $\left(\begin{array}{l}n\\1\end{array}\right)=\left(\begin{array}{l}n\\n-1\end{array}\right)=n$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.